Implementasi Aplikasi Sarana Prasarana dan Alat Kesehatan Studi: Puskesmas Purnama Kecamatan Pontianak Selatan Kota Pontianak - Hangga Taqwa Reza; Martoyo Martoyo; Herlan Herlan (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
The effective management of infrastructure and medical equipment is a vital factor in improving the quality of public health services. However, manual management systems still in place often create various obstacles, such as reporting delays, difficulties in monitoring equipment conditions, and suboptimal procurement planning. This research utilizes a qualitative method with a descriptive-analytical approach. Data collection was conducted through in-depth interviews with the Pontianak City Health Office, the head of the Puskesmas (Community Health Center), infrastructure management officers, and health workers, as well as direct observation and documentary studies. The implementation of the application was analyzed based on the process of implementing the Infrastructure and Medical Equipment Application at the Purnama Community Health Center, using George C. Edwards III’s policy implementation framework, which focuses on four key variables: Communication, Resources, Disposition, and Bureaucratic Structure.The research results indicate that the implementation of the infrastructure and medical equipment application has had a positive impact on the management system at the Purnama Community Health Center. However, the findings reveal several challenges: Communication: Transmission, clarity, and consistency are not yet operating optimally. Resources: ASPAK (Medical Equipment and Infrastructure Application) officers are not general personnel, and the internet network remains inadequate or unstable. Disposition: There is a lack of official decrees from the Head of the Health Center regarding the ASPAK Team. Bureaucratic Structure: To ensure effective, efficient, and accountable implementation, Standard Operating Procedures (SOPs) or workflows must be established; currently, the lack of a routine meeting agenda suggests that the bureaucratic structure is not yet sufficiently developed.